EXPRESSÕES DE VIOLÊNCIAS NA ESCOLA, TENSÕES SOCIAIS E “RACIAIS”: MINHA PRESENÇA O INCOMODA? - Julyana Sueme Winkler Oshiro (2024)
School violence is a serious problem that affects millions of students worldwide, with negative consequences for their physical and mental health, as well as their academic and social performance. The thesis of this research was that the social and "racial" tensions established in the school were a significant factor in the occurrence and configuration of violence in the school environment. The aim was to investigate, from the incident logs of the ninth grade classes A, B, and C of secondary school, the expressions of violence in the school environment in light of social and "racial" tensions. We chose a state school in Campo Grande, Mato Grosso do Sul, as the field of study. More specifically, the objectives of this study were to identify the types of violence present in the educational context; to investigate how social and "racial" tensions impact the manifestation of violence in the school, focusing on patterns and trends; and to verify which social groups are more vulnerable (victims) to violence in the ninth grade and which are more likely to perpetrate it (aggressors). For a more in-depth analysis, efforts were focused on the incidents in the ninth grade classes, considering this as the final transition stage between secondary and high school, when subjective and objective demands intensify for the individuals involved. In this study, a qualitative methodological approach with documentary and bibliographic characteristics was adopted. The collected/generated data and content were analyzed based on the Critical Theory of Society, using the postulates of Theodor W. Adorno, cultural studies, and the contributions of Freudian psychoanalysis in dialogue with social studies and those addressing the topic of racism. This methodology allowed us to obtain a broad and deep understanding of the complexity of social and "racial" relations in the school and their relation to the manifestations of violence ("racial," verbal, physical, psychological, patrimonial, and sexual). The hypothesis of this research was that the social and "racial" tensions established in the ninth grades were a significant factor in the continued occurrence and configuration of the violence that individuals suffered and perpetuated. Therefore, the explanation and analysis of such violence found their privileged locus in this transition from secondary to high school, an essential stage for the constitution of objectified subjectivities in different contexts. The results indicated that expressions of violence were present in different social groups, which we termed: whites and non-whites for a powerful conceptual operation. Violent behaviors often reflected attitudes and values present in society, such as authoritarianism and racism. The data analysis largely flirted with the initial hypothesis that the social and "racial" tensions established in the ninth grades were a significant factor in the occurrence and configuration of violence in the school environment. The research identified a relationship between the social layer and "race" of the students with an inflection to the subject who practices or suffers the violence. This ambivalence present in the same subject reaffirms the social tensions related to violence, that is, no matter how much the victims practice certain types of violence, they remain the same in terms of suffering. In a word, the profile of the victims remains the same from a social, gender, and "racial" point of view. The apprehension and confrontation of the different manifestations and forms of violence demanded specific contextual strategies that could use messianic violence as a mechanism for inhibiting violence in the educational context. Our findings also indicate that if it is in early childhood that we can "diagnose" violence, it can be affirmed that it is in the transition from the ninth grade to high school that it intensifies (when it gains speed). Keywords: School violence; Expressions of violence; Social and “racial” tensions.